2009
DOI: 10.5380/rsa.v10i5.15185
|View full text |Cite
|
Sign up to set email alerts
|

O Sistema Radicular Da Variedade Rb855536 De Cana-De-Açúcar No Plantio Em Minitolete E Tolete

Abstract: Este trabalho teve como objetivo estudar o desenvolvimento radicular de cana-de-açúcar em dois sistemas de plantio, minitolete e tolete. O experimento foi realizado na Estação Experimental de Paranavaí, no município de Paranavaí-PR, Setor de Ciências Agrárias, Universidade Federal do Paraná, no período de 27 de junho de 2000 a 10 de julho de 2001. Foi utilizado delineamento em blocos ao acaso, com duas formas de plantio. Foram 9 épocas de avaliações durante o ciclo de 378 dias. A forma de plantio e a profundid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 4 publications
(5 reference statements)
0
3
0
3
Order By: Relevance
“…However, the distribution of root length observed in the treatment TWI levels were more homogeneous in the soil profile compared to irrigated treatments, which showed greater root length in the region near the emitter tube (Figure 3). BUSO et al (2009) also observed a decrease in root length as to increase the depth in the soil profile. SANTOS (2010) states that subsurface drip irrigation provides a more homogeneous distribution of roots in the profile, different cultivation without irrigation where there is a predominance of roots in the first layer.…”
Section: Root Lengthmentioning
confidence: 73%
“…However, the distribution of root length observed in the treatment TWI levels were more homogeneous in the soil profile compared to irrigated treatments, which showed greater root length in the region near the emitter tube (Figure 3). BUSO et al (2009) also observed a decrease in root length as to increase the depth in the soil profile. SANTOS (2010) states that subsurface drip irrigation provides a more homogeneous distribution of roots in the profile, different cultivation without irrigation where there is a predominance of roots in the first layer.…”
Section: Root Lengthmentioning
confidence: 73%
“…The study includes both cane-plant and ratoon cane, between 1997 and 2009: crop coefficients (Kc) were recommended by Allen et al (1998), whose periods were fitted to the developmental stages proposed by Machado et al (2009), and the rooting system effective depth (z) was recommended by Buso et al (2009) (Table 1).…”
Section: Methodsmentioning
confidence: 99%
“…After harvest, each plant was separated into stem and top+leaves, which were labeled and placed in an oven at 60°C to obtain the dry weight (Oliveira, 2008). Total leaf area (TLA m 2 ) was determined by measuring from the first to the sixth leaf of eight plants in two linear meters of sampling area in each experimental plot, measuring leaf length and width in the middle portion with a graduated ruler, using the equation TLA=L.W.c proposed by Buso et al (2009), where L= length; W= width; c=correction factor. Biometric data were collected to determine parameters related to plant production following the method proposed by Barbosa (2005), where the number of plants was obtained by counting the plants sampled in two linear meters of each plot, and mean stem height was measured with a graduated ruler, measuring plant height from ground level to the top.…”
Section: Description Of the Experimental Sitementioning
confidence: 99%